Globoid cell leukodystrophy (Krabbe disease) in a Merino sheep. (January 2019) - Lee, Effie; Fuller, Maria; Carr, Mandi; Manavis, Jim; Finnie, John
We describe the clinicopathologic features of an ovine case of Krabbe disease (globoid cell leukodystrophy). Brain lesions, sometimes bilaterally distributed, were present in the cerebellar peduncles, cerebellar folia white matter, medulla, pons, and spinal cord and characterized by marked myelin loss and numerous large macrophages (globoid cells), which tended to aggregate perivascularly. Gemistocytic astrocytes were abundant, and their nuclei were frequently abnormal. The activity of the deficient enzyme, galactosylceramide β-galactosidase, was undetectable in this neurologic disorder compared to age- and breed-matched control brains, and levels of the neurotoxic substrate, psychosine, were markedly elevated.